Salvage of Upper Limb following a Severe Crushing Trauma: Immediate Reconstruction with a Free Flap and Subsequent Hyperbaric Oxygen Therapy - M. P. Serra; P. Longhi (Case Reports in Medicine)
A microsurgical latissimus dorsi flap was performed for resurfacing a large soft tissue defect of the forearm with exposure of the vital structures and contaminated wound. Early coverage of a defect is a generally accepted concept to achieve a better functional result. The authors present a case report where a free latissimus dorsi flap with subsequent hyperbaric oxygen therapy allowed a successful single stage reconstruction of this complex severely contaminated defect.